2019
DOI: 10.1177/1461348419846722
|View full text |Cite
|
Sign up to set email alerts
|

Coupled vibration characteristics of a submarine propeller-shaft-hull system at low frequency

Abstract: The coupled longitudinal and transverse vibration characteristics of a submarine propeller-shaft-hull system at low frequency are studied in this paper. Two substructures, which are the propeller-shaft subsystem and the submarine hull, are first modelled using the finite element method. The two substructures are then connected through bearings, which are simplified as longitudinal and lateral springs and dampers. The modes, the natural frequencies and the coupled vibration characteristics of the two substructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
0
0
2
Order By: Relevance
“…Многие не обладают наглядными и быстрыми способами расчета и подбора необходимых при проектировании установки параметров ее элементов, составляющих сочетание системы автоматики дизеля и часто принимаемой в расчетах механической трех-массовой части (ТМЧ) комплекса [6,7,8]. Необходимо отметить, что при этом приходиться упрощать систему дифференциальных уравнений и уменьшать точность расчета [9,10,11].…”
Section: вступлениеunclassified
See 1 more Smart Citation
“…Многие не обладают наглядными и быстрыми способами расчета и подбора необходимых при проектировании установки параметров ее элементов, составляющих сочетание системы автоматики дизеля и часто принимаемой в расчетах механической трех-массовой части (ТМЧ) комплекса [6,7,8]. Необходимо отметить, что при этом приходиться упрощать систему дифференциальных уравнений и уменьшать точность расчета [9,10,11].…”
Section: вступлениеunclassified
“…В тоже время для расчета более сложных систем для определения резонансных частот необходимо применять методы, не обладающие наглядностью и требующие длительного подбора оптимальных составляющих пропульсивной установки [7,8,11,12]. Например, таким перспективным методом расчета является широко применяемый матричный метод.…”
Section: вступлениеunclassified
“…To account for overall ship hull structure vibration, a combination of several damping components was considered for total damping in their study. More on the dynamics studies in the propeller shaft system can be found in the literature [11][12][13].…”
Section: Introductionmentioning
confidence: 99%